A study of barriers in healthcare waste management sector - Raj A.; Samuel C. (My University, 2025)
The World Health Organization (WHO) identified healthcare waste as highly infectious and a threat to the environment and human health. India’s current healthcare waste management system has certain limitations, which lead to ineffective waste handling practices. Hence, the purpose of this paper is to, first, identify the critical barriers that hinder India’s healthcare waste management (HCWM) systems. Secondly, define all barriers into four quadrants depending upon their driving and dependence power and at last classified them as cause and effect. HCWM system barriers were identified through the literature, field surveys, and brainstorming sessions. The hierarchal and contextual relationships among the barriers were analysed using interpretive structural modelling (ISM). Using the decision-making trial and evaluation laboratory (DEMATEL), barriers are classified as cause and effect. In total, 15 HCWM system barriers were identified and placed in seven different ISM model hierarchy levels, and eight barriers are found as the cause. The model will help hospital managers and pollution control boards to make policies and find out the mutual relationship and interlinking among the barriers. Copyright © 2023 Inderscience Enterprises Ltd.